Electrocatalysis of Lindane Using Antimony Oxide Nanoparticles Based-SWCNT/PANI Nanocomposites - Masibi, Kgotla K.; Fayemi, Omolola E.; Adekunle, Abolanle S.; Sherif, El-Sayed M.; Ebenso, Eno E. (Frontiers in Chemistry, 2018)
This work describes the chemical synthesis of antimony oxide nanoparticles (AONPs), polyaniline (PANI), acid functionalized single-walled carbon nanotubes (fSWCNTs) and the nanocomposite (AONP-PANI-SWCNT) as catalyst for the trace detection of lindane. Successful synthesis of the nanomaterials was confirmed by Fourier transform infrared (FT-IR) spectroscopy, ultraviolet-visible (UV-Vis) spectroscopy, x-ray diffraction (XRD) spectroscopy and scanning electron microscopy (SEM). Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used for investigating the electrochemical behaviour of the modified electrodes in the ferrocyanide / ferricyanide ([Fe(CN)6]4-/[Fe(CN)6]3-) redox probe. GCE-AONP-PANI-SWCNT exhibited faster electron transport properties as well as higher electroactivity as compared to bare-GCE, GCE-AONPs, GCE-PANI, and GCE-SWCNT electrodes. Electrocatalytic studies further showed that GCE-AONP-PANI-SWCNT modified electrode was stable (after 20 scans) with only a small current drop in lindane (0.57%). The GCE-AONP-PANI-SWCNT electrode with low detection limit of 2.01 nM performed better towards the detection of lindane as compared to other studies in literature. The GCE-AONP-PANI-SWCNT electrode is highly selective towards the detection of lindane in the presence of various organic and inorganic interfering species. Real sample analysis of river water and tap water samples using the developed sensor gave satisfactory percentage recoveries therefore confirming the potential of the proposed sensor for practical application.